Comparative anatomy of the Sapajus sp. (bearded capuchin) hand with comments on tool use in a parallel evolution with the hominid pathway - Bretas, Rafael; Freitas-Ferreira, Emmanuel; Souto Maior, Rafael; Tomaz, Carlos; Gonçalves-Mendes, Maria Tereza; Aversi-Ferreira, Tales Alexandre (Frontiers in Physiology, 2024)
Bearded capuchins display a wide variety of manipulatory skills and make routine use of tools in both captivity and the wild. The efficient handling of objects in this genus has led several investigators to assume near-human thumb movements, despite a lack of anatomical studies. Here, we performed an anatomical analysis of muscles and bones in the capuchin hand. Sapajus morphological traits were quantitatively compared with those of humans, chimpanzees, gorillas, and baboons. The comparative analysis indicated that the Sapajus hand is more similar to that of baboons and least similar to that of humans according to the muscles, bones and three-dimensional data. Furthermore, these findings suggest bearded capuchins lack true thumb opponency. Regarding manipulatory skills, they display rather primitive hand traits, with limited resources for precision grasping using the pollicis opponens. These findings suggest that bearded capuchins' complex use of tools depends more heavily on their high cognitive abilities than on a versatile hand apparatus. These findings offer crucial insights into the evolution of primate cognition.